2018
DOI: 10.1002/lary.27629
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cryotherapy on vocal fold healing in a rabbit model

Abstract: Objectives/Hypothesis Cryotherapy has been shown to be a scarless treatment modality for dermal lesions; however, there are limited data addressing the effect of cryotherapy on vocal fold tissue. The aim of this study was to clarify the effectiveness of cryotherapy for prevention of postsurgical vocal fold scarring. Study Design Prospective animal study in rabbits. Methods The lamina propria of 20 rabbit vocal folds was bilaterally stripped, followed by randomized unilateral cryotherapy. Five larynges were har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…Dysregulation of TGF‐β and its isoforms following VF injury is one of the primary mechanisms underlying the development of fibrosis 27,28 . Many fibrotic conditions are characterized by sustained and excessive TGF‐β signaling, resulting in altered ECM metabolism and fibroblast–myofibroblast differentiation 29,30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation of TGF‐β and its isoforms following VF injury is one of the primary mechanisms underlying the development of fibrosis 27,28 . Many fibrotic conditions are characterized by sustained and excessive TGF‐β signaling, resulting in altered ECM metabolism and fibroblast–myofibroblast differentiation 29,30 .…”
Section: Resultsmentioning
confidence: 99%
“…Dysregulation of TGF-β and its isoforms following VF injury is one of the primary mechanisms underlying the development of fibrosis. 27,28 Many fibrotic conditions are characterized by sustained and excessive TGF-β signaling, resulting in altered ECM metabolism and fibroblast-myofibroblast differentiation. 29,30 In the early stages of the wound-healing process, TGF-β modulates complex interactions among fibroblasts, inflammatory cells, and TGF-β signaling.…”
Section: Modulation Of Vf Fibrosis By the Tgf-β Familymentioning
confidence: 99%
“…82 Because scarring is the primary cause of poor postoperative voice quality, cryotherapy's potential to produce minimal scarring yields high potential as a treatment for laryngeal lesions. Gong et al 15 found that cryotherapy in a rabbit model simulates an environment similar to that of the fetal wound-healing environment, which is characterized by minimal inflammation, rapid re-epithelialization, and reduced collagen formation. Knott et al 84 found both reduced collagen formation with more organized structure after application of cryotherapy, along with decreased keratinization.…”
Section: Tissue Effectsmentioning
confidence: 99%
“…The use of steroids, proton pump inhibitors and TNF-α have been advocated [195]. Moreover, cryotherapy promoted regeneration and reduced inflammation and fibrosis in larynxes of rabbits [196]. Thereafter, all of the abovementioned treatments should be investigated in radiationinduced dysphonia context.…”
Section: Dysphagia and Dysphoniamentioning
confidence: 99%